The peculiarities of the university students’ value preferences - Sobkova, Svitlana; Sobkov, Yuriy (Virtus, 2017)
The article under discussion reveals the peculiarities of the university students' value preferences that have been determined in the course of empirical research. The obtained data refer to certain students' categories at various stages of their studies at the university. All the values have been ranked as the ones with high, medium, and low degrees of significance. Besides, the article determines the difference in the system of students' values according to the level of their socialization. The results of the investigation have been described for Ukrainian and Romanian students (the representatives of ethnic minorities) in ethnically homogenous and heterogeneous groups. The very system of students' values has been considered within the studies of the students' socialization peculiarities.
Keywords: socialization, the system of values, value preferences, the levels of socialization, ethnic minority